The Use of Slang in the Business Environment - Maciej WIDAWSKI (Communications of International Proceedings, 2021)
While jargon is widely considered to be the essential subset of lexicon used in business communication, slang is another important subset, albeit largely marginalized in both scholarly and business literature. In contrast to jargon, this highly informal vocabulary serves different purposes than the mere exchange of information. Aside from the mere referential function, slang is used in place of standard expressions to convey extra information of a rhetorical, sociological, or psychological nature. Slang in the business environment can also be used for similar reasons. This database-driven sociolinguistic paper analyzes numerous uses of slang, grouped according to the above functions, and amply illustrated with relevant citational corroboration from diverse sources with rich business content. In that, it highlights the usefulness of slang which – along with jargon – can be successfully employed to facilitate business communication.
Keywords: lexicon; slang; informality; business; communication